An Examination of Author Characteristics in National and Regional Criminology and Criminal Justice Journals, 2008–2010: Are Female Scholars Changing the Nature of Publishing in Criminology and Criminal Justice? - Crow, Matthew S. (American journal of criminal justice, 2015)
Criminology and criminal justice (CCJ) as an academic discipline has experienced an increase in the focus on various aspects of academic productivity in recent years. Much of the extant literature examining journal article authorship has focused on various measures of the publication productivity of specific authors but not on the characteristics of the authors themselves. The current study expands upon previous work by examining several author characteristics across different journal types and research methodologies, with a particular focus on how gender relates to these issues. The findings reveal several interesting differences with regard to gender, academic rank, and university affiliation. Among these findings is evidence that although males are more likely to author CCJ articles regardless of journal type, females are more likely to be lead authors in regional journal articles and more likely to publish with other female authors. Regional journals are also the publication outlet of choice for students and assistant professors in the beginning of their careers. The findings also provide evidence of important differences in author rank, academic affiliation, methodology, and publication outlet for articles authored by females.